Employee Performance Analysis at the Office of the Civil Service and Human Resources Development Agency of Central Bengkulu Regency - Rikardo, Yanuar; Lorita, Evi; Handayani, Tuti; Julianti, Yeni Dwi (Utan Kayu Publishing, 2023)
Study This aiming For analyze performance employee office For human resource development and human resources in Central Venkle Regency. This study use method qualitative . Informant the following are involved in study This is : (1) employee permanent BKPSDM center Bengkulu, (2) central Bengkulu people who understand BKPSDM soft skills understand and know that they involved direct through BKPSDM Bengkulu Central Skill Skills. Researchers choose kind of studies qualitative , so that the data received must clear and specific (Sugiyono, 2007: 22). If the data source is viewed from data sources , data collection can shared become three : observation , interviews , and documents . Based on findings research and discussion about skills employee For increase performance Benkul Central BKPSDM, research This show importance develop soft skills for increase performance employees at the agency human resource development and central human resources from Benkul Regency (BKPSDM). Skills like effective communication , ability adapt , thinking critical , work team , and leadership is factor main supporting productivity and efficiency work . Employees who can manage time they , finish problem , and show empathy and integrity proven give service public best . In addition , training management stress and presence well employee strengthen focus work and create environment harmonious work . This study also emphasizes that leadership participatory promote motivation and performance team. With training sustainable , BKPSDM can increase ability employees , creating culture positive work and present challenge more organization good . In Overall , soft skill acquisition is not only increase performance individual , but also supports achievement objective strategic organization and quality service more public tall.